EXPERIMENTAL MANIPULATION WHICH INTERFERES WITH THE PHENOTYPIC EXPRESSION OF THE DYSTROPHIC PROCESS: CROSS REINNERVATION OF A FAST TWITCH MUSCLE BY THE NERVE OF A SLOW TONIC MUSCLE IN CHICKENS WITH HEREDITARY MUSCULAR DYSTROPHY - Mazliah, Jacob (My University, 1980)
Hereditary muscular dystrophy of the chicken is a primary defect of muscle which is expressed specifically in the fast twitch, focally innervated glycolytic muscle, while slow tonic, multiply innervated oxidative muscles are spared disease characteristics (for review, Cosmos et. al., 1979b). Since motor nerves influence the characteristics of skeletal muscles, and since slow tonic muscles in the chicken do not express dystrophic phenotypes, it was decided to replace the motor innervation of the fast twitch posterior latissimus dorsi (PLD) muscle with the motor innervation of the slow tonic anterior latissimus dorse (ALD) muscle within a dystrophic chicken, in order to alter the fate of the dystrophic fast twitch muscle. Selected mechanical, histochemical and structural properties of the ALD and PLD muscles of normal (White Leghorn) and dystrophic (Storrs line) chickens 15-800 days ex ovo were compared to determine which of these properties were altered as a result of the disease, and to provide baseline data for the analysis of the cross reinnervation experiments. ALD muscles of dystrophic chickens exhibited normal phenotypes, i.e. slow tonic isometric contraction in response to nerve stimulation in vivo, acid and alkaline stable myosin ATPase activity, "en grappe" innervation, weak phosphorylase (Pase), strong succinic dehydrogenase (SDH) enzymic activities and peripheral location of nuclei. PLD muscles of dystrophic genotype demonstrated structural and histochemical alterations but retained contraction and relaxation times characteristic of fast twitch muscle of normal genotype. Further, they exhibited focal "en plaque" innervation and alkaline stable myosin ATPase activity similar to that of normal PLD muscles. The abnormalities identified in the dystrophic PLD included the following: lower muscle weight, abnormal size and shape of fibres, increased number of internal nuclei, abnormal Pase and SDH enzymic activities and lower twitch and tetanic tensions. The surgical cross reinnervation between the ALD nerve and the PLD muscle was performed at hatching. The muscles were examined at various time intervals postoperatively using the criteria established in the study of the unoperated muscles. Self reinnervation of PLD muscles by their own nerves, and cross reinnervation with normal chickens served as control experiments. Fibres of both normal and dystrophic PLD muscles which had been successfully cross reinnervated acquired mechanical, structural and histochemical properties characteristic of the ALD muscle. Thus, muscles of both genotype responded similarly to the ALD nerve. These results established that the PLD muscle of dystrophic chicken is able to accept the new innervation, and is as capable of responding to the influence of the ALD nerve as is the normal PLD. Furthermore, the successfully cross reinnervated fibres are spared disease characteristics. The present cross reinnervation experiment demonstrates, for the first time, an experimental manipulation which interferes with the expression of phenotypic characteristics of dystrophy during development ex ovo. The results support the rationale underlying the present study: the PLD muscle of dystrophic genotype is unable to respond appropriately to the demand from its own motor nerve to complete successfully the transition from embryo to adult metabolism, thus expressing the dystrophic phenotypes. However, when this request is removed by cross reinnervating the PLD muscle with the ALD nerve, the dystrophic phenotype is not expressed. These findings strongly suggest that regardless of the time during development when slow tonic characteristics are achieved, i.e. either during development in ovo or by surgical manipulation ex ovo, slow tonic fibres are spared dystrophic phenotypes.
Keywords: Medical Sciences; Medical Sciences